2001
DOI: 10.1034/j.1600-0773.2001.d01-169.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Supplementation Efficiently Reduces Lead Absorption in Suckling Rats*

Abstract: The effect of calcium supplementation on tissue lead was evaluated in suckling Wistar rats. Such data are not yet available in the literature. The following artificial feeding regimen was used for calcium supplementation: cow's milk by addition of 1%, 3% or 6% Ca as CaHPO 4 ¿2H 2 O suspension to increase the daily calcium intake about 1.4, 2 or 3 times above control values. Artificial feeding was applied during 7 hr each day for nine consecutive days (from day 6 through 15 after birth). The effect of such trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
5
15
0
Order By: Relevance
“…These results, which are in agreement with our previous experiments (Varnai et al, 2001a), confirm the findings of other authors that calcium primarily reduces lead absorption and does not significantly influence lead elimination (Barton et al, 1978;Quarterman et al, 1978). ), 72 h prior to beginning the Ca and DMSA treatments.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results, which are in agreement with our previous experiments (Varnai et al, 2001a), confirm the findings of other authors that calcium primarily reduces lead absorption and does not significantly influence lead elimination (Barton et al, 1978;Quarterman et al, 1978). ), 72 h prior to beginning the Ca and DMSA treatments.…”
Section: Discussionsupporting
confidence: 95%
“…Calcium supplementation caused an increase in carcass calcium, as noticed earlier (Varnai et al, 2001a), but in this experiment it was not statistically significant. The decrease in copper values in DMSA-treated pups is in agreement with previous data (Tandon et al, 1983;Smith et al, 2000), because it is known that DMSA is also used as a chelating agent for enhancing copper elimination (Ding & Liang, 1991;Ren & Yang, 1997).…”
Section: Discussionsupporting
confidence: 56%
“…Quarterman and Morisson (1975) established that the absorption and retention of lead in rats is especially influenced by Ca and phosphate which both decrease the retention and increase the excretion of lead. Meredith et al (1977), Bogden et al (1992) and more recently Varnai et al (2001) also showed that higher Ca intake might be a way of reducing Pb absorption in rats. In the same way, Quaterman et al (1978), Spickett and Bell (1983) and more recently Cortina-Ramirez et al (2005) also showed that increased dietary phosphate limits Pb intestinal absorption in rats.…”
Section: Acute Toxicity Genotoxicity and Bioaccumulation Of Lead In mentioning
confidence: 92%
“…In addition, calcium supplementation in human infants was reported to inversely correlate with absorption and retention of lead (Ziegler et al 1978). Experimental studies on calcium supplementation in suckling rats have been conducted and significant decrease of lead in all tissues and increase in carcass calcium have been reported, but no effects on trace elements in tissues and the general appearance and the body weight gain of the sucklings were observed (Varnai et al 2001).…”
Section: Introductionmentioning
confidence: 97%